Photoinduced 1,2-Hydro(cyanomethylation) of Alkenes with a Cyanomethylphosphonium Ylide - Miura, Tomoya; Moriyama, Daisuke; Funakoshi, Yuuta; Murakami, Masahiro (Synlett, 2019)
An efficient method has been developed for the 1,2-hydro(cyanomethylation) of alkenes, in which a cyanomethyl radical species is generated from a cyanomethylphosphonium ylide by irradiation with visible light in the presence of an iridium complex, a thiol, and ascorbic acid. The cyanomethyl radical species then adds across the C=C double bond of an alkene to form an elongated alkyl radical species that accepts a hydrogen atom from the thiol to produce an elongated aliphatic nitrile. The ascorbic acid acts as the reductant to complete the catalytic cycle.
Keywords: alkenes; nitriles; photocatalysis; radicals; phosphonium ylides; hydro(cyanomethylation)